Routine Laser-assisted Indocyanine Green Angiography in Immediate Breast Reconstruction: Is It Worth the Cost? - Mirhaidari, Shayda (Plast Reconstr Surg Glob Open, 2019)
BACKGROUND: Laser-assisted indocyanine green angiography (LAIGA) has been proven to accurately detect mastectomy skin flap necrosis (MSFN) intraoperatively and prevent postoperative complications in breast reconstruction. The purpose of this study was to examine the cost-effectiveness of the routine use of LAIGA in immediate breast reconstruction and to perform a break-even point analysis. METHODS: This is a retrospective review of prospectively gathered data from all patients who underwent immediate breast reconstruction from January 2014 to January 2015. LAIGA was routinely used in all cases. Patients were followed for at least 90 days to capture postoperative complications. Costs were calculated by reviewing itemized bills and Medicare Reimbursement Current Procedural Terminology codes to assess surgeon fees. Outcomes and costs were compared with a historical cohort of patients who underwent breast reconstruction before the implementation of LAIGA. RESULTS: Two-hundred-and-six immediate breast reconstructions (126 patients) were performed using LAIGA for a total cost of $210,700. The average cost of MSFN in our LAIGA cohort was $30,496. The routine use of LAIGA decreased the MSFN rate from 12.4% to 6.3% and prevented MSFN on 13 breasts resulting in a gross cost savings of $396,453, and net savings of $185,753. Break-even point analysis demonstrated that number of cases needed to break even decreases as the average MSFN cost and MSFN reduction rate increase. CONCLUSION: The routine use of LAIGA in immediate breast reconstruction is cost-effective in reducing the incidence of MSFN, implant loss, and overall unexpected reoperation rate.